Supplementation of serum albumin is associated with improved pulmonary function: NHANES 2013–2014 - Hu, Sheng; Guo, Qiang; Wang, Silin; Zhang, Wenxiong; Ye, Jiayue; Su, Lang; Zou, Sheng; Zhang, Deyuan; Zhang, Yang; Yu, Dongliang; Xu, Jianjun; Wei, Yiping (Frontiers in Physiology, 2022)
Background: The serum albumin level is reflective of the function of multiple organs, such as the liver and kidneys. However, the association between serum albumin and pulmonary function is unclear; therefore, this study aimed to determine the relationship between pulmonary function and serum albumin, including the threshold of serum albumin at the changes of the pulmonary function in the total population and in different strata of population. Methods: In this cross-sectional study, We examined the relationship between serum albumin and two independent indicators of pulmonary function: forced vital capacity (FVC) and forced expiratory volume in one second (FEV 1), using data from National Health and Nutrition Examination Survey (NHANES 2013-2014) (n=3286).We used univariate analysis, stratified analysis, and multiple regression equation analysis to examine the correlation between serum albumin levels and FVC and FEV 1, and performed smoothed curve fitting, threshold effect, and saturation effect analysis (for stratification) to determine the threshold serum albumin level at which FVC and FEV 1 begin to change. Results: The adjusted smoothed curve fit plot showed a linear relationship between serum albu-min levels and FVC: for every 1 g/dL increase in the serum albumin level, FVC increased by 80.40 ml (11.18, 149.61). Serum albumin and FEV 1 showed a non-linear relationship. When serum al-bumin reached the inflection point (3.8 g/dL), FEV 1 increased with increasing serum albumin and the correlation coefficient β was 205.55 (140.15, 270.95). Conclusions: Serum albumin is a core indicator of liver function, and abnormal liver function has a direct impact on pulmonary function. In the total population, serum albumin levels were linearly and positively correlated with FVC. Above 3.6 g/dL, serum albumin was positively correlated with FEV 1. Based on the total population and different population strata, this study revealed a positive association between the serum albumin level and pulmonary function, and identified the threshold of serum albumin when Indicators of pulmonary function tests starts to rise, providing a new early warning indicator for people at high risk of pulmonary insufficiency and has positive implications for the prevention of combined respiratory failure in patients with liver insufficiency.